Evaluation of the effectiveness of the complex of diagnostic and therapeutic measures in patients with anomalies of the dentoalveolar apparatus accompanied by phonetic disorders - Мельник, Альона Олександрівна (Actual Dentistry, 2019)
Summary. During the examination of orthodontic patients, there are children with phonetic disorders. Only the elimination of anatomical defects does not lead to the normalization of articulation of sounds. This requires close collaboration between the orthodontist and the speech therapist, with the involvement of specialists from other profiles if necessary. Objective. To propose and evaluate the effectiveness of the complex of diagnostic and therapy measure in patients with dentoalveolar anomalies and deformations, accompanied by phonetic disorders. Material and methods of investigation. One hundred and sixty children with existing and non-existing dentoalveolar anomalies and deformations of the dentoalveolar apparatus were examined for the development of the diagnostic and therapeutic complex. Methods of the study were used: clinical; rhinoscopy, pharyngoscopy, otoscopy, tonal and speech audiometry, tympanometry, anthropometry, cephalometry, electromyography, computer tomography; study of a semiotic component of speech, statistical. Results of the research and their discussion. Confirmed that otorhinolaryngologic diseases are an additional risk factor for the formation of dentoalveolar anomalies and a confounding factor in orthodontic treatment. Phonetic changes in dentoalveolar anomalies were studied. Removable and fixed equipment was used to eliminate orthodontic pathologies. Most patients were diagnosed with a narrowing of the jaws in the lateral areas, which leads to the forced retention of the tongue in the lower back position. In addition, standard vestibular plates Dr. Hinz – MUPPY-P with a bead, removable orthodontic apparatus, Bluegrass appliances were used and devices for eliminating and preventing harmful language habits were proposed. After speech correction, the correct articulation was formed and positive functional, morphological and aesthetic changes were achieved during orthodontic treatment. Conclusions. The proposed device contributes to the training of the muscular structures of the articulation apparatus. The complex of diagnostic and therapeutic measures can increase the effectiveness of orthodontic treatment of children with dental anomalies due to a multidisciplinary approach. Key words: anomalies and deformations of the dentognathic apparatus, phonetic disorders.